Analysis of Community-Based Waste Management Policies to Achieve Clean and Healthy Environment - Musiana Musiana; Sitti Nurhidayanti Ishak; Maya Sari Soamole; Diah Merdekawati Surasno (West Science Interdisciplinary Studies, 2024)
This research aims to analyze community-based waste management policies as an effort to create a clean and healthy environment. Using the literature review method, this research explores various aspects of waste management policies, the role of communities in policy implementation, and their impacts on the environment and public health. The findings indicate that an approach involving active community participation, integration of social justice aspects, technological utilization, and sustainable evaluation are crucial in achieving effective and sustainable waste management. These findings provide valuable insights for formulating future waste management policies, with an emphasis on the importance of a holistic approach involving all stakeholders.